N‐Acyl ethanolamide and eicosanoid involvement in irritant dermatitis. (1st July 2016) - Kendall, A.C.; Pilkington, S.M.; Sassano, G.; Rhodes, L.E.; Nicolaou, A.
Summary: Background: Sodium lauryl sulfate (SLS) and ultraviolet radiation (UVR) are two commonly encountered cutaneous inflammatory stimuli. Differing histopathological and clinical features implicate involvement of alternative inflammatory pathways; bioactive lipid mediators (eicosanoids, endocannabinoids and sphingolipids) are likely candidates for regulation of the divergent inflammatory responses. Objectives: To assess comprehensively bioactive lipid involvement in SLS‐ and UVR‐induced inflammatory responses, to provide a better understanding of bioactive lipid mediator pathways in irritant inflammation. Methods: Buttock skin from 10 healthy volunteers was treated with two minimal erythema doses of UVR (275–380 nm, peak 305 nm) or an SLS dose optimized for each individual, to produce a comparable, moderate erythema. Punch biopsies were taken 24 h postchallenge and from untreated skin, and separated into dermis and epidermis. Lipids [including 15 prostanoids, 15 hydroxy fatty acids (HFAs), nine endocannabinoids and related N ‐acyl ethanolamides (NAE), and 21 sphingolipids] were extracted and quantified using liquid chromatography–tandem mass spectrometry. Results: Increased epidermal NAE and HFA expression was observed in response to SLS but not UVR‐induced low‐level inflammation. Significant changes following SLS treatment included augmented levels of NAE, possessing proinflammatory and some reported anti‐inflammatory properties, with 3·7‐fold ( P = 0·02) and threefold ( P = 0·01) increased expression of palmitoyl and stearoyl ethanolamides, respectively, in addition to 1·9‐fold ( P = 0·02) increased expression of 12‐hydroxyeicosatetraenoic acid. Conclusions: The differential bioactive lipid upregulation implicates their involvement in skin irritant responses, potentially reflecting roles in inflammatory cell recruitment and subsequent resolution of inflammation, giving scope for new treatment approaches to irritant dermatitis.